UNIVERSITAS INDONESIA SYSTEM SUPPORT IN ACCELERATING LECTURERS TO IMPLEMENT ODEL FACILITIES - T. Ahmad Danial; Irma Septuriany Dewanti; Dimas Septian Saputra (Universitas Terbuka, 2023)
Directorate of Academic Advancement and Learning Resources Universitas Indonesia (DPASDP UI) established in 2020 and one of sub-directorate